"Assessment of Skin Damage Appearance and Its Causes after Open Heart Surgery in Khatam-ol-Anbia Hospital during Second Half of the Year 1379" - M ADJALOOIAN; A ZARINARA; A KOKAB; A FEIZZADEH; F ALAEDINI (Tehran University of Medical Sciences, 2002)
To evaluate the quality of services in hospitals can rely on mortality rate and side effects rate. According to performed studies, side effects rate is a better indicator to evaluate the quality of hospital services, therefore decreasing of side effects is one of the main objectives in hospital management. A side effect of open-heart surgery is the skin damage. Some of Iranian patients who were operated on this kind of surgery have appeared some skin damages that medical articles haven't pointed this matter. This study was performed to assess the appearance rate and also causes of skin damages to promote the services quality of Khatam-ol-Anbia Hospital in Tehran. During 6 months particulars of patients, who were operated on the open-heart surgery were considered. The data regarding the patients from their medical files and the data about skin damages rate from Nursing reports was collected. The skin damages were divided four groups on the basis of damage intensity: without damage; with skin redness; blustery; and intense phlogestic (inflamed). 102 patients (%28.2) somewhat suffered from skin damages. Among these 102 patients, 88 patients (%87.1) were affected with slight skin redness; 5 patients (%5) with intense skin redness; 5 patients (%5) with blister; and 3 cases with intense burn like damages. Generally, %1.4 of patients suffered from blister and %0.8 of cases from intense burn like damages; it means one case among every 50 patients needed special attention. In this study, the factors of weight, gender, diabetes, narcotics addiction, and function of one of the first aid of surgeon influenced the skin damage. It deserves to pay attention to the rate of patients' losses and compensation amount, which must be, paid the patients by hospitals. It seems if the above mentioned matters are considered the importance of this study will be cleared more.